A non-invasive method for the routine-estimation of fresh weight of cells grown in batch suspension cultures. - Blom, T.J.M.; Kreis, Wolfgang; van Iren, F.; Libbenga, K.R. (Plant Cell Reports, 1992)
A simple apparatus was designed to allow sedimentation of plant cells grown in batch suspensions in Erlenmeyer flasks. After sedimentation the height of the cell mass along the glass wall was measured with a ruler fixed in the apparatus. The cell volume after sedimentation, calculated from this height, appeared highly correlated with the fresh weight of cells. This result was found with eight cell lines in two Laboratories. The method proved to be very suitable to allow routinely measurement of FW without the destruction of cells, from many samples, in a short time, during each phase of the growth cycle. © 1992 Springer-Verlag.
UnivIS-Import:2015-03-05:Pub.1992.nat.dbio.LPB.anonin